Linking Health IT and Learning Organization to Sustainable Hospital Performance: Mediating Effect of Adaptive Agility Strategy - Tresia Mahaputeri Nusantari Maghfirah; Denny Bernardus; Cliff Kohardinata; Halek Mu'min (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines whether Adaptive Strategy Based Agility (ASBA)—a novel construct synthesizing Dynamic Capability Theory and Institutional Theory—mediates the effects of Health Information Technology (HIT) and Learning Organization (LO) on Sustainable Hospital Performance (SHP) in Indonesian hospitals, addressing prior inconsistent findings on HIT's direct performance effects. Design/methodology/approach – Data were collected from 240 respondents (hospital directors and senior management) across 80 hospitals in Jakarta, Bandung, Semarang, and Surabaya, three respondents per hospital, using a seven-point Likert questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 to test seven hypothesized relationships spanning direct effects, antecedent-to-ASBA paths, and ASBA's mediating role. Findings/Results – All five direct paths were statistically significant and positive. HIT and LO each had significant direct and indirect effects on SHP, both classified as complementary (partial) mediation through ASBA, which itself was the strongest single predictor of SHP. The model also showed meaningful out-of-sample predictive relevance via PLSpredict and CVPAT. Originality/Value – The study contributes theoretically by integrating Dynamic Capability Theory and Institutional Theory within a single mediating construct (ASBA), and practically by clarifying how hospitals can convert technological and learning-based resources into sustained performance through deliberate, institutionalized strategic agility.